SOLUCION ESTADÍSTICA PARA UNA ANOMALIA EN EL CÁLCULO DE LA ENERGÍA INTERNA DE UN SISTEMA COMPUESTO, EN EL CONTEXTO DE LA MECÁNICA ESTADÍSTICA NO-EXTENSIVA - Reyes Navarro, Felipe Américo (2009)
Therein, inside of 3rd. version of nonextensive statistical mechanics, a generalization of the standard Boltzmann-Gibbs-Shannon statistics, we display a solution to an anomaly found in the calculation of internal energy for a composite A+B, 2 spins ½ with additive Hamiltonian H = HA + HB, specifically, by calculating internal energy in full Hilbert space is different to calculating it into the Hilbert subspaces, in other words, U ≠ UA +UB. We make as much analytical calculations (for 2 spins ½), as computational simulations (for spins SA=2 and SB= 2/3). The results indicate, of exact way, that the alternative method of matrices EA and EB is exact for the calculations with internal energy, therefore, ρq is the matrix that contains the physical information of the system but not the matrix ρ, as happen in the standard statistical.